(untitled) - Shelton, Hal (Rockville, Maryland, 2014)
This book "is packed with actionable advice and real-life examples from Shelton's experience as a senior executive, SCORE small business mentor, and angel investor."
Keywords: Doanh nhân,Kinh doanh nhỏ,Entrepreneurship,Small business